Analysis of urban growth effects on Land Surface Temperature (LST) increase using GIS: A case study of Chelghoum El Aïd city (1984-2024) - Zaari Achouak; Djeffal Djafar (Glasnik Srpskog Geografskog Društva, 2025)
The city of Chelghoum El Aïd has experienced rapid urban growth, primarily driven by a major urbanization event. This expansion has prioritized the development of natural and undeveloped spaces, rather than investing in urban infrastructure. As a result, there has been a significant transformation of open areas, leading to a considerable reduction in green and natural spaces. In addition to the environmental impact, the urban expansion of Chelghoum El Aïd has become more pronounced from a morphological perspective. This is characterized by the densification of existing urban fabric and the gradual transformation of its original structure. The city continues to expand beyond its initial boundaries, gradually integrating previously undeveloped areas. This study analyzes the urban growth of Chelghoum El Aïd (Wilaya of Mila, Algeria) from a morphological perspective the city’s growth has predominantly followed a linear and compact pattern along National Road No. 5 to highlight the role of urban form in the emergence of urban heat islands. The research employs across-evaluation of Land Surface Temperature (LST) and the Normalized Difference Vegetation Index (NDVI), utilizing satellite imagery spanning the period from 1984 to 2024. The analysis is based on data from Land sat sensors 5, 8, and 9, processed using ArcGIS 3.2.0 software. The correlation results indicate an inverse relationship between LST and NDVI indices. The year 1984 showed the strongest negative correlation (R² = 0.3466) and the steepest regression slope (-42.33) demonstrating that the decrease in vegetation cover has significantly contributed to the rise in temperatures within Chelghoum El Aïd, Since the beginning of the study period, temperatures have risen by approximately three degrees Celsius. This study benefits key stakeholders, including ministries (environment, agriculture, energy), universities and research centers, municipalities, environmental organizations, and the private sector. These entities use the findings to enhance urban planning, resource management, and sustainable development.